Correlation between perceived coaching behaviors and motivational climate in female collegiate tennis players - Flores, Margaret Agnes G. 1997-; Valleser, Christian Wisdom M. (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2024)
This study takes this finding as an initial hypothesis in determining the significant correlation between the different coaching behaviors and motivational climate of collegiate women tennis players participating in the annual University Athletic Association of the Philippines or UAAP. The researcher aims to identify the kind of coaching style prevalent in the various UAAP tennis teams and measure the levels of players’ motivation in their respective teams. A total of 31 collegiate women tennis players participated in this study answering the questionnaires entitled ‘Leadership Scale for Sports™ and ‘Perceived Motivational Climate Scale-2’. The Statistical Package for Social Sciences (SPSS) software was used for the data analysis, the Measures of Central Tendency to describe the results of the study, and Spearman Rank Correlation Test to determine the relationship between the subscales of the two research instruments. Results in this study revealed that the players perceive their coach as having training and instruction, positive feedback, and democratic behavior often. and occasionally showing autocratic and social support behavior. The players also agree that they have experienced task-involving motivation and they neither agree nor disagree in experiencing ego-involving motivational climate throughout the season. It also showed that there is a significant correlation between training‘ & instruction/task-involving motivation and positive feedback/task-involving motivation. On the other hand, democratic behavior/task-involving motivation, training and instruction/ego-involving motivation, and positive feedback/ego-involving motivation have no significant correlation
Thesis (Bachelor of Sports Science) -- University of the Philippines Diliman
Includes bibliographical references
Keywords: Coach-athlete relationship; Women tennis player